2020
DOI: 10.11336/jjcrs.11.91
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of finger movement characteristics in dementia patients using a magnetic sensing finger-tap device

Abstract: Objective: Differences in finger movement characteristics during finger-tapping movements among Alzheimer's Disease (AD) patients, Mild Cognitive Impairment (MCI) patients, and healthy elderly individuals were examined using a magnetic sensing finger-tap device (UB-2; Maxell, Tokyo), and relationships with cognitive function were investigated. Methods: Finger-tapping movements were measured and multiple comparisons using mean values of parameters from each group were conducted. Cognitive function was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Bimanual finger-tapping was performed for 15 s as quickly and widely as possible [ 24 ]. The distance between the thumb and index finger during the finger-tapping movement was measured using a magnetic sensor at 100 Hz (UB-2, Maxell, Ltd., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Bimanual finger-tapping was performed for 15 s as quickly and widely as possible [ 24 ]. The distance between the thumb and index finger during the finger-tapping movement was measured using a magnetic sensor at 100 Hz (UB-2, Maxell, Ltd., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…However, of the 44 parameters measured, those that differed significantly in interhemispheric inhibition varied widely from study to study. Table 2 presents the conditions of the hand-tapping task, measured parameters, individuals compared with the measured parameters, method of comparison, and parameters for which significant differences were found and reported in the studies from the PubMed database [45,[49][50][51][52][53][54], in which elderly individuals and children were the participants and a magnetic sensor-type finger-tapping device was used. Future studies identifying at least one promising measurement parameter from the aforementioned 44 parameters for evaluating interhemispheric inhibition using the magnetic sensor finger-tapping device are warranted.…”
Section: (1) Unilateral Finger-tapping Task Performed With the Nondom...mentioning
confidence: 99%
“…In particular, improved finger movement ability leads to improved activities of daily living in older adults with dementia [55], and studies investigating the relationship between bimanual coordination movements and cognitive function have gained attention in recent years. Several studies have compared individuals with Alzheimer's disease (AD) or mild cognitive impairment (MCI) with healthy elderly individuals [49,50,54]. In one such study, Suzumura et al compared and verified the motion characteristics of bimanual coordinated movement in 173 MCI patients and 173 healthy elderly subjects using a magnetic sensor finger-tapping device [54].…”
Section: Bimanual Coordinated Movements and Agingmentioning
confidence: 99%
“…We have conducted preliminary studies on finger movements in patients with dementia based on the fact that hand movements may detect pathological changes in the brain at an early stage. Accordingly, we detected finger movement features with cognitive decline; finger dexterity declines at AD and MCI stages compared to healthy conditions [15][16][17][18][19]. In a study of cognitive function and hand function at other institutions, it was reported that the number of finger taps decreased and that the tapping interval increased in patients with AD and MCI than in healthy older adults [20].…”
Section: Introductionmentioning
confidence: 99%